Interactive and Social Reading Intervention in Design-based Research - Sanal, Seda Oher (Univ Malaga, 2023)
This study, carried out within the design-based research framework, aimed to create a digital environment for students with learning problems to read better. The social constructivist approach was used in this study, which generally focuses on the assumption that reading is an active, interactive, dynamic, and social language skill. The instructional content, built on a learning management system, was developed in line with this strategy. Focus on the problem, understand the problem, define the design goals, outline the solution, create the solution, and test the solution stages. This results in effective and efficient digital teaching material that students with learning problems can use in their reading processes. The study clearly showed the development process of digital material, as well as a deep theoretical discussion.
Keywords: Reading research; technology integration; constructivism; learning